Land Use and Spatial Planning in Puncak Area Bogor - Satori, Ahmad; Sjahbana, Joesron Ali (Universitas Ibn Khaldun Bogor, 2025)
Puncak area, located in Bogor, is known as one of the main tourist destinations as well as an important conservation area for the ecosystem in the Jabodetabek area. With its crucial ecological role as a water catchment and flood control area, this area faces rapid development pressures, especially for the tourism and housing sectors. This study explores changes in land use and spatial planning in Puncak area and their impacts on environmental quality and the socio-economic well-being of local residents. This article results show that the conversion of green land into built-up areas, such as housing and tourism facilities, has reduced environmental quality, increased disaster risks, and changed the socio-economic structure of the community. In addition, inconsistencies in spatial planning and weak supervision of regulatory implementation have further exacerbated this situation. Therefore, a more comprehensive and sustainable spatial management approach is needed to maintain the balance between development and environmental conservation in this area.